Clinical Follow-Up without Radiographs Is Sufficient after Most Nonoperatively Treated Distal Radius Fractures in Children - Marja Perhomaa; Markus Stöckell; Tytti Pokka; Justus Lieber; Jaakko Niinimäki; Juha-Jaakko Sinikumpu (Children, 2023)
Distal forearm fractures are common in children and are usually treated nonoperatively. No consensus has been reached on how to perform clinical and radiographic follow-up of these fractures. Our aim was to study whether radiographic and clinical follow-up is justified. We included 100 consecutive patients with non-operatively treated distal forearm fractures who were treated at Oulu University Hospital in 2010–2011. The natural history of the fractures during the nonoperative treatment was analyzed by measuring the potential worsening of the alignment during the follow-up period. The limits of acceptable fracture position were set according to the current literature using “strict” or “wide” criteria for alignment. We determined the rate of worsening fracture position (i.e., patients who reached the threshold of unacceptable alignment). In relation to splinting, we evaluated how many patients benefited from clinical follow-up. Most of the fractures (98%) preserved acceptable alignment during the entire follow-up period when wide criteria were used. The application of stricter criteria for alignment in radiographs showed loss of reduction in 19% of the fractures. Worsening of the alignment was recognized at a mean of 13 days (range 5–29) after the injury. One in three (32%) patients needed some intervention due to splint loosening or failure. Radiographic follow-up of nonoperatively treated distal forearm fractures remains questionable. Instead, clinical follow-up is important, as 32% of patients needed their splints fixed.